Rational-emotive and cognitive-behavior therapy (REBT/CBT) versus pharmacotherapy versus REBT/CBT plus pharmacotherapy in the treatment of major depressive disorder in youth; A randomized clinical trial. Issue 3 (28th February 2015) - Iftene, Felicia; Predescu, Elena; Stefan, Simona; David, Daniel
Abstract: Major depressive disorder is a highly prevalent and debilitating condition in youth, so developing efficient treatments is a priority for mental health professionals. Psychotherapy (i.e., cognitive behavioral therapy/CBT), pharmacotherapy (i.e., SSRI medication), and their combination have been shown to be effective in treating youth depression; however, the results are still mixed and there are few studies engaging multi-level analyses (i.e., subjective, cognitive, and biological). Therefore, the aims of this randomized control study (RCT) were both theoretical - integrating psychological and biological markers of depression in a multi-level outcome analysis - and practical – testing the generalizability of previous results on depressed Romanian youth population. Eighty-eight ( N =88) depressed Romanian youths were randomly allocated to one of the three treatment arms: group Rational Emotive Behavior Therapy (REBT)/CBT (i.e., a form of CBT), pharmacotherapy (i.e., sertraline), and group REBT/CBT plus pharmacotherapy. The results showed that all outcomes (i.e., subjective, cognitive, and biological) significantly change from pre to post-treatment under all treatment conditions at a similar rate and there were no significant differences among conditions at post-test. In case of categorical analysis of the clinical response rate, we found a non-significant trend favoring group REBT/CBT therapy. Results of analyses concerning outcome interrelations are discussed. Highlights: We ran a randomized clinical trial (RCT) for major depressive disorder (MDD) in youths. We analyzed multiple-level outcomes (i.e., subjective, cognitive, and biological) across groups. Youths ( N =88) were randomly allocated to: group REBT/CBT, medication, or their combination. Results showed a similar pattern across groups on all levels of analysis.